2012
DOI: 10.1371/journal.pone.0031263
|View full text |Cite
|
Sign up to set email alerts
|

Reference Genes for Accurate Transcript Normalization in Citrus Genotypes under Different Experimental Conditions

Abstract: Real-time reverse transcription PCR (RT-qPCR) has emerged as an accurate and widely used technique for expression profiling of selected genes. However, obtaining reliable measurements depends on the selection of appropriate reference genes for gene expression normalization. The aim of this work was to assess the expression stability of 15 candidate genes to determine which set of reference genes is best suited for transcript normalization in citrus in different tissues and organs and leaves challenged with fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
207
2
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(237 citation statements)
references
References 47 publications
18
207
2
10
Order By: Relevance
“…UPL7 was confirmed as a reference gene for Citrus spp. infected with viruses (Mafra et al 2012). In our study, UPL7 expression exhibited the highest stability in salt-stressed roots and cold-and heat-stressed leaves, while the lowest stability was in heat-stressed roots ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…UPL7 was confirmed as a reference gene for Citrus spp. infected with viruses (Mafra et al 2012). In our study, UPL7 expression exhibited the highest stability in salt-stressed roots and cold-and heat-stressed leaves, while the lowest stability was in heat-stressed roots ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Semi-quantitative reverse transcription polymerase chain reaction (RT-PCR) using SAND gene (Mafra et al 2012) as normalizer was performed. RT-PCR was carried out using Eppendorf Mastercycler (Serial No.…”
Section: Expression Profiling Of Citarf Citaux/iaa and Citgh3 Genesmentioning
confidence: 99%
“…Mafra et al (2012) analyzed the stability of 15 candidate reference genes in various tissues and organs of Citrus plants infected with several pathogens, including C. liberibacter and Xylella fastidiosa. FBOX (F-box family protein, which regulates cellular processes such as cell cycle transition, transcriptional regulation, and signal transduction), SAND (SAND protein family, which regulates intracellular vesicle transport), GAPC2 (GAPDH C2, which participates in the metabolism of glucose), and UPL7 (ubiquitin ligase 7 protein, which functions in protein trafficking) were demonstrated to be the most stable in all of the conditions and samples tested by Mafra et al (2012). When the analysis was conducted with samples from C. liberibacter-infected plants, TUB was the least stable gene, which is similar to what we observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The instability of reference gene expression may result in an over-or under-estimation of target gene expression . Gene expression studies in animals (Small et al, 2008) and plants, including Citrus species (Kou et al, 2012;Mafra et al, 2012;Yan et al, 2012), have demonstrated that even genes considered to have a constitutive expression exhibit variation in expression under different experimental conditions, which requires an a priori determination of the stability of reference gene candidates, depending upon the conditions to be evaluated.…”
mentioning
confidence: 99%